PENGAMATAN KADAR MERKURI DI PERAIRAN TELUK KAO (HALMAHERA) DAN PERAIRAN ANGGAI (PULAU OBI) MALUKU UTARA - Edward, Edward (Makara Journal of Science, 2008)
Observation on Mercury Concentration in Kao Bay (Halmahera) and Anggai Waters (Obi Island), North of Maluku. Observation on merkuri concentration in territorial waters of Kao Bay and Anggai have been done in January 2005. The result showed that mercury concentration in seawater and sediment in territorial waters of Kao Bay and Anggai waters still lower and still in line with peaceful threshold value for waters biota life. This data indicate that waste of mercury coming from activity of gold mining by PT Nusa Halmahera Raya (NHR) and illegal gold mining by society not yet polluted both of that waters.